Post-operative evaluation of Eagle’s syndrome and comparison of symptomatic relief with styloid excision versus styloid fracture - Gandham, Madhuri; Dhayalan, Swathi; N. S., Prakash; S., Swathi Kamal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: This study was done to evaluate symptomatic relief of patients with Eagle’s syndrome post-surgical treatment, and to compare the symptomatic relief in the styloid process excision with fracture of styloid process transorally. Methods: A sample size of 25 patients was taken and each patient was counselled regarding surgical treatment: styloid process excision (styloidectomy), or fracture of styloid process, using transoral approach. Patients were then followed up and evaluated based on symptomatic relief, particularly pain while swallowing and throat pain using numerical rating scale. Results: Majority of participants (56.8%) were in the 31-40 age range. The sample was predominantly female, comprising 86.4% of the participants, while males comprised 13.6%. All participants reported throat pain as their primary complaint. Radiating pain varied, with 43.2% of participants reporting headaches, followed by pain radiating to the ear (11.4%) and the jaw (4.5%). The preoperative pain levels were at a mean of 7.70±1.11, which decreased post operatively to 7.11±1.13 on day 0, 4.55±1.61 on day 7, and 3.73±1.91 after 12 weeks. There was no statistically significant difference in the mean reduction of numeric rating scale (NRS) scores between the excision and fracture groups (p=0.868). Conclusions: Styloidectomy is an effective method for treating Eagle’s syndrome. Both styloid process excision and fracture of styloid process, through transoral route, are equally effective in providing symptomatic relief to patients with Eagle’s syndrome.